PERAN MANAJEMEN KINERJA DALAM MENINGKATKAN EFEKTIVITAS PERUSAHAAN PADA PT. X - Meisy Nanik; Agus Wahyudi; Alfina Rahmawati; Mariyatul Qibliyah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research discusses the role of performance management in increasing company effectiveness at PT. X. In an era of increasingly tight business competition, company effectiveness is the main key to achieving long-term success. Performance management is a systematic process that aims to improve individual and team performance in an organization. The role of performance management is not only limited to measuring work results, but also includes developing a positive and results-oriented organizational culture. This research uses a quantitative descriptive approach with a sample of 35 people from a total population of 55 PT employees. X. Data collection techniques are carried out through observation and interviews. Through the use of effective performance management, companies are not only able to identify and overcome existing problems, but can also create new opportunities for growth. Thus, performance management becomes an integral component in a company's development strategy, which in turn can contribute significantly to business effectiveness and sustainability.